2021
DOI: 10.1002/cpt.2379
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the miRNA‐mRNA Interactome in Human Hepatocytes and Identification of Functional mirSNPs in Pharmacogenes

Abstract: MiRNAs regulate the expression of hepatic genes involved in pharmacokinetics and pharmacodynamics. Genetic variants affecting miRNA binding (mirSNPs) have been associated with altered drug response, but previously used methods to identify miRNA binding sites and functional mirSNPs in pharmacogenes are indirect and limited by low throughput. We utilized the high‐throughput chimeric‐eCLIP assay to directly map thousands of miRNA‐mRNA interactions and define the miRNA binding sites in primary hepatocytes. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In addition, another regulator of gene expression are the Micro RNA (miRNAs), where genetic variations in miRNA binding sites are associated with an altered drug response [98]. In a similar vein, a recent publication by Powell et al reported the mapping of miRNA-mRNA interactions in several pharmacogenes, in fact, the authors identified an hsa-mir-27b-DPYD interaction at a previously validated binding site, which may suggest the existence of additional elements that contribute to the individualism of drug response [99].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, another regulator of gene expression are the Micro RNA (miRNAs), where genetic variations in miRNA binding sites are associated with an altered drug response [98]. In a similar vein, a recent publication by Powell et al reported the mapping of miRNA-mRNA interactions in several pharmacogenes, in fact, the authors identified an hsa-mir-27b-DPYD interaction at a previously validated binding site, which may suggest the existence of additional elements that contribute to the individualism of drug response [99].…”
Section: Discussionmentioning
confidence: 97%
“…Currently, no systematic data are available to identify the functional significance of miRNAs, and methods to identify miRNA binding sites are indirect and time consuming. To address this gap, application of the chimeric‐eCLIP assay recently described to map the hepatocyte miRNA‐mRNA interactome 117 should be explored to identify miRNAs binding to transporter mRNAs in hepatocytes and cells in other organs. Another class of regulatory RNAs that is understudied are the lncRNAs.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…We previously reported that (1) AGT mRNA is endogenously bound by miR‐122‐5p in human hepatocytes using the mir‐eCLIP assay and that (2) rs699 A > G significantly decreases reporter mRNA levels in hepatocytes using the high‐throughput functional screening assay PASSPORT‐seq 34 . Since microRNAs bind to and decrease mRNA abundance, our assay results suggest miR‐122‐5p decreases AGT mRNA more with the rs699 A > G variant.…”
Section: Introductionmentioning
confidence: 61%
“…The ViennaRNA suite version 2.4.14 38 was used to call RNAduplex with default settings to test the effect of rs699 A > G on binding strength. The miR‐122‐5p sequence was obtained online from miRbase (https://www.mirbase.org/cgi-bin/mirna_entry.pl?acc=MI0000442), and the AGT region of rs699 was obtained from the PASSPORT‐seq oligo sequence used to clone the reporter construct 34 . This sequence included complementary primer ends which were included in the analysis to make sure miR‐122‐5p was not predicted to target these.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation